2017
DOI: 10.1021/acs.inorgchem.6b02340
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Structural and Electronic Properties of Medium-Sized Sodium Clusters: A Honeycomb-Like Na20 Cluster

Abstract: Sodium is one of the best examples of a free-electron-like metal and of a certain technological interest. However, an unambiguous determination of the structural evolution of sodium clusters is challenging. Here, we performed an unbiased structure search among neutral and anionic sodium clusters in the medium size range of 10-25 atoms, using the Crystal structure AnaLYsis by Particle Swarm Optimization (CALYPSO) method. Geometries are determined by CALYPSO structure searches, followed by reoptimization of a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 50 publications
6
48
0
Order By: Relevance
“…Binding energy per atom ( E b ) is employed to measure the total thermodynamic stability of a cluster . E b of a cluster is calculated by using the equation: Eb()AlxTiyNiz=E()AlxTiyNizitalicxE()AlitalicyE()TiitaliczE()Nix+y+z. …”
Section: Resultsmentioning
confidence: 99%
“…Binding energy per atom ( E b ) is employed to measure the total thermodynamic stability of a cluster . E b of a cluster is calculated by using the equation: Eb()AlxTiyNiz=E()AlxTiyNizitalicxE()AlitalicyE()TiitaliczE()Nix+y+z. …”
Section: Resultsmentioning
confidence: 99%
“…Studies of the structure of Na 20 using DFT molecular dynamics 64,83 or an empirical potential 84 followed by DFT optimization found a ground state structure with C s point symmetry. However, a recent study 63 using a particle swarm optimization method found a Na 20 structure with C 3 point symmetry which was lower in energy than the C s structure by 60 meV (Møller-Plesset MP2 theory) or 150 meV using a CCSD method.…”
Section: E Na20mentioning
confidence: 99%
“…Guet and Johnson 30 using a similar approach found similar optical absorption at 2. with C s or C 3 symmetry using coordinates from Ref. [63]. The shell structure of occupied and virtual levels in a spherical jellium structure is 1s 2 1p 6 1d 10 2s 2 1f 0 2p 0 2d 0 .…”
Section: E Na20mentioning
confidence: 99%
See 1 more Smart Citation
“…Clusters are gas phase nano‐sized aggregates of matter, they are vitally important for technological advances, and can serve as model systems to untangle and simplify the investigation of otherwise intractable problems at the fundamental level using a combination of theoretical and experimental methods. The contributions along these two lines are so numerous that it would be impossible to provide a meaningful comprehensive review of the literature within the confines of a research article. One fundamental issue that can be addressed theoretically and experimentally using clusters is the determination of the nuclear quantum effects on the dynamics and thermodynamics of microsolvation.…”
Section: Introductionmentioning
confidence: 99%